2018
DOI: 10.2147/cmar.s157661
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FOXO6 in breast cancer promotes epithelial–mesenchymal transition and facilitates migration and proliferation of cancer cells

Abstract: PurposeIncreasing evidence indicates that members of forkhead transcription factor family (FOXO) play key roles in cell proliferation and apoptosis in multiple cancers, including prostate cancer. However, the underlying mechanism of FOXO6 was not yet known. The aim of our work is to investigate the function of FOXO6 in breast cancer.MethodsIn the present study, quantitative real-time polymerase chain reaction and Western blotting analyses were used to detect the expression of FOXO6 in breast cancer tissues and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…17,18 In this study, we showed that In our previous study, we reported FOXO6 is downregulated in breast cancer, the function of which is to regulate migration, invasion, and epithelial-mesenchymal transition through transcriptionally regulated Sirt6 expression. 19 As Li, W. 20 reported that FOXN3 was a transcriptional repressor and promoted progression of hormonally responsive breast cancer through inhibition of GATA3. Interestingly, although we revealed that FOXN4 is another tumor driver, the mechanism is distinct.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In this study, we showed that In our previous study, we reported FOXO6 is downregulated in breast cancer, the function of which is to regulate migration, invasion, and epithelial-mesenchymal transition through transcriptionally regulated Sirt6 expression. 19 As Li, W. 20 reported that FOXN3 was a transcriptional repressor and promoted progression of hormonally responsive breast cancer through inhibition of GATA3. Interestingly, although we revealed that FOXN4 is another tumor driver, the mechanism is distinct.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that FOXOs are involved in regulating cell migration is further supported by the observation that FOXO6 regulates Plxna4-mediated neuronal migration during development [ 76 ]. However, when overexpressed, FOXO6 has also been shown to inhibit breast cancer cell migration and invasion [ 77 ]. These conflicting findings may reflect the cell type–specific roles of FOXOs in cell migration and metastasis.…”
Section: Tumour-suppressive Roles Of Foxosmentioning
confidence: 99%
“…Forkhead transcription factor family (FOXO) are tumour suppressor regulating cell proliferation and promoting apoptosis in BC. Recent in vitro studies have demonstrated that expression of FOXO6 promotes BC migration and invasion by aiding EMT [114]. Elevated FOXO6 in BCs could be, at least in part, due to reduced activity of the PI3K/AKT pathway.…”
Section: Key Lvi-related Biomarkersmentioning
confidence: 99%